MORPHOLOGICAL STUDY OF NOTOCOTYLUS JAMSHORENSIS N.SP. (TREMATODA: NOTOCOTYLIDAE) FROM MALLARD ANAS PLATYRHYNCHOS OF HAMAL LAKE OF PAKISTAN (The Research of Medical Science Review, 2024)
A total of 16 trematodes of genus Notocotylus were collected from the intestine of 12 host Anas platyrhynchos collected from Hamal Lake, Sindh, Pakistan. These trematodes were identified as Notocotylus jamshorensis n. sp. based on basic diagnostic characteristics including body shape and size, lateral rows and median rows, the arrangement of glands, shape, and size of testes and ovary, the distance between the ovary and anterior extremity of the hind body, distribution of Vitellaria and post-testicular space and other differentiating characters with its congeners. The new species name states Jamshoro city. Species of genus Notocotylus previously reported from Pakistan include N. panjnadensis Bhutta and Khan, 1975 collected from intestine of Anas crecca; N. sindhensis Khan et al., 2017 collected from intestine of Anas platyrynchos.